2021
DOI: 10.1136/bmjresp-2021-000987
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of nurses caring for respiratory patients during the first wave of the COVID-19 pandemic: an online survey study

Abstract: BackgroundNurses have been at the forefront of the pandemic response, involved in extensive coordination of services, screening, vaccination and front-line work in respiratory, emergency and intensive care environments. The nature of this work is often intense and stress-provoking with an inevitable psychological impact on nurses and all healthcare workers. This study focused on nurses working in respiratory areas with the aim of identifying and characterising the self-reported issues that exacerbated or allev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 30 publications
4
31
0
2
Order By: Relevance
“…The search strategy used achieved an initial retrieval of 11,031 potential articles for the study, out of which 32 articles were finally included in the final sample (Table 1 Once the 32 selected studies had been evaluated (Table 1), it was observed that more than half of the articles stemmed from the Americas: Canada (3,35), The USA (1, 23-30, 34, 37, 45), Brazil (47) and one article that refers to the American continent in general (3); the rest of the evidence is distributed across studies from Asia (10, 14,32,38,40,40,42,43,43,44,49), Europe (39,41,46), Oceania (6,31,48), and Africa (33); therefore, all the articles are written in English. Regarding the journals where these articles were published, it was noted that all were published in journals indexed in the Proquest, Scopus, and Pubmed databases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The search strategy used achieved an initial retrieval of 11,031 potential articles for the study, out of which 32 articles were finally included in the final sample (Table 1 Once the 32 selected studies had been evaluated (Table 1), it was observed that more than half of the articles stemmed from the Americas: Canada (3,35), The USA (1, 23-30, 34, 37, 45), Brazil (47) and one article that refers to the American continent in general (3); the rest of the evidence is distributed across studies from Asia (10, 14,32,38,40,40,42,43,43,44,49), Europe (39,41,46), Oceania (6,31,48), and Africa (33); therefore, all the articles are written in English. Regarding the journals where these articles were published, it was noted that all were published in journals indexed in the Proquest, Scopus, and Pubmed databases.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the evidence also reports that there are enabling factors for the performance of the role, firstly, when it is considered that these professionals provide "constructive" support with their work (38); in addition, they are resilient, capable of self-care and adaptability towards the continuous changes in protocol and scarcity of resources (42), as well as their capacity for planning, support, information, active participation in research and adequate use of resources (39), relevant aspects that should be considered by the employers of healthcare services, since they must ensure clear practices in the care to be provided, control measures for infections and personal protection equipment that is adequate for the use of healthcare providers, which are all indispensable variables to en-sure the health of healthcare providers and their families (28); in addition, the need for psychological support for these professionals is also evident (48), as well as the need for their continuing education. This need should not only satisfy nurses but also other healthcare providers who are for the implementation of programs and protocols with the objective of minimizing cross-infection for patient and staff safety in the face of a pandemic (10, 33,48), strengthening interdisciplinary work (46). One strategy reported in this review that will undoubtedly support their performance in improving communication with isolated populations is telehealth.…”
Section: S14mentioning
confidence: 99%
See 1 more Smart Citation
“…From the experiences with the severe acute respiratory syndrome virus (SARS) outbreak in the early 2000’s, it has been demonstrated that ICU professionals may need long term support for mental health issues developed during their work time with infected patients [ 25 ]. As recently proposed by other authors [ 26 , 27 ], intervention plans should be traced not only during the pandemic but also after it, due to the prolonged course of diseases such as PTSD, ASD, and SA. For that reason, we believe that this study could be used for guiding larger, multicenter studies and institutional interventions to prevent and reduce the suffering of professionals dealing with similar situations in Brazil and in other countries.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report from the United Kingdom also shows that in the early stages of the COVID-19 pandemic, many nurses felt strong concerns about their work environment (especially in infection control), maintaining nursing quality, and maintaining mental health. It has also been found that there is inadequate access to systems to care for them ( 11 ). International surveys have also shown that health care workers feel strong psychological stress in the early stages of the COVID-19 pandemic, and this is especially true for young female health care workers ( 12 ).…”
Section: Discussionmentioning
confidence: 99%